Microbial enrichment, functional characterization and isolation from a cold seep yield piezotolerant obligate hydrocarbon degraders. Issue 9 (21st May 2020) - Van Landuyt, Josefien; Cimmino, Lorenzo; Dumolin, Charles; Chatzigiannidou, Ioanna; Taveirne, Felix; Mattelin, Valérie; Zhang, Yu; Vandamme, Peter; Scoma, Alberto; Williamson, Adam; Boon, Nico
ABSTRACT: Deep-sea environments can become contaminated with petroleum hydrocarbons. The effects of hydrostatic pressure (HP) in the deep sea on microbial oil degradation are poorly understood. Here, we performed long-term enrichments (100 days) from a natural cold seep while providing optimal conditions to sustain high hydrocarbon degradation rates. Through enrichments performed at increased HP and ambient pressure (AP) and by using control enrichments with marine broth, we demonstrated that both pressure and carbon source can have a big impact on the community structure. In contrast to previous studies, hydrocarbonoclastic operational taxonomic units (OTUs) remained dominant at both AP and increased HP, suggesting piezotolerance of these OTUs over the tested pressure range. Twenty-three isolates were obtained after isolation and dereplication. After recultivation at increased HP, an Alcanivorax sp. showed promising piezotolerance in axenic culture. Furthermore, preliminary co-cultivation tests indicated synergistic growth between some isolates, which shows promise for future synthetic community construction. Overall, more insights into the effect of increased HP on oil-degrading communities were obtained as well as several interesting isolates, e.g. a piezotolerant hydrocarbonoclastic bacterium for future deep-sea bioaugmentation investigation. Abstract : An obligate oil degrader was found together with easy-to-grow consorts after enriching a cold seep sediment at pressures simulating 1000 m underwater.